PERANAN PROGRAM KOPERASI JASA KEUANGAN SYARIAH BAITUL MAAL WAT TAMWIL ( KJKS BMT) DALAM PEMBERDAYAAN PELAKU USAHA MIKRO KECIL MENENGAH DI KOTA PADANG - Rizki Afri Mulia (Ensiklopedia Social Review, 2019)
This research background was found in the implementation of the program Baitul Maal Wat Tamwil (BMT) in Empowerment’s actors UMKM in Padang. The aims of this research was to describe the implementation of Sharia Baitul Maal Wat Tamwil (KJKS BMT) Cooperative Program and to know the impact of KJKS Program implementation through savings and loan program in approaching the access of business capital to SMEs in Padang City. The method used in this research was qualitative research using descriptive method. The research found that the Role of Sharia Financial Services Cooperative Program Baitul Maal Wat Tamwil (KJKS BMT) for the Empowerment of Micro Small Medium Enterprises has been effective by providing financing in the addition of venture capital to UMKM for the development of their business. Although the implementation of KJKS program has been in accordance with existing procedures but has not fully able to improve the welfare of its members. This can be seen from its still found some obstacles in the implementation, constraints faced can be categorized into two forms. Internal obstacles such as: lack of KJKS capital, poor people's mindset about KJKS program, lack of supervision on KJKS program implementation, external constraints such as: the utilization of aid funds that have not maximized, Fructuative Community Economic Condition (unstable), Competitor with product Just like the existence of loan sharks, obstacles that come from the participants of the program carried out efforts such as guidance, the system pick up the ball against members who are stuck in the payment.